2019
DOI: 10.1111/ecc.13109
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attitude and knowledge towards resuscitation and advance care planning at the palliative care unit

Abstract: Objective There is a lack of information about patients’ attitudes towards and knowledge of resuscitation and advance care planning (ACP) in the palliative care unit (PCU). The aims of this study were to examine (a) patients’ attitudes towards and knowledge of the topic of resuscitation, (b) patients’ level of education about their illness and (c) their concept of ACP. Methods This study used a qualitative methodology that involved semi‐structured interviews with advanced cancer patients admitted to the PCU. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…However, only 9.4% of our study samples had signed a DNR order (Table 1). Previous studies demonstrated that medical condition is one of the most important factors affecting the signature of a DNR order [7,8,13,17]. The low percentage can be explained by the reason that our study sample came from general medical and surgical inpatients who are not at immediate risk of death.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, only 9.4% of our study samples had signed a DNR order (Table 1). Previous studies demonstrated that medical condition is one of the most important factors affecting the signature of a DNR order [7,8,13,17]. The low percentage can be explained by the reason that our study sample came from general medical and surgical inpatients who are not at immediate risk of death.…”
Section: Discussionmentioning
confidence: 97%
“…The results are congruent with previous studies, in which people considered that discussions about DNR orders were stressful, being worried about the possible undertreatment, neglect, or even abuse from the process of treatment [8,11,12]. Sometimes, in order to relieve the distress and uneasiness, this stress would be modulated by defense mechanisms (e.g., inappropriate thinking or behavior, thinking that it is too early or unnecessary to make an end-of-life decision, or belief that it is others' responsibility) [7,8,13,14,17]. In addition, after putting all three factors into a logistical regression with the enter method, the factor of 'stress, avoidance, and ignorance' was the only independent predictor of participating in the discussion regarding end-of-life CPR/DNR orders (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This plan includes various recommendation to analyze policy assessment on care directives and improve ACP for PLWD (WHO, 2018). Part of this improvement effort with ACP includes education efforts to help caregivers and PLWD understand the disease and caregiving journey and the encouragement to ask the right questions during ACP for the discussion of the detailed aspects of future care treatment and medical interventions (Sellars et al, 2019;Unself et al, 2019;and Ashton et al, 2016). The importance of education indicates an aspect of caregiving since they are faced with the possibility of learning new skills to care for their loved one, from learning how to do safe transfers to nurse-trained skills like foley-catheter changes and simple, preventative wound care.…”
Section: Introductionmentioning
confidence: 99%